Фраземіка Соломонових «Приповідок» - Пілько, О. (Лексикографічний бюлетень, 2011)
In the article the author analyzes the phraseological units from Solomon`s proverbs, focusing most attention on ones with somatic components. For the source edition the translation of the Bible by I. Khomenko has been chosen (the «Roman Bible»). The semantic and grammatical aspect, objectification of reality through the phraseological map of the world, nomination of procedurality, and perception / non-perception of experience of human life has under you special consideration. The somatic code of culture corresponds with archetypical imagination of man. The anthropocentrism of phraseology is seen as a set of constants defining the microcosm, the nominational processes having as their important component the so called «somatisms», because human evaluation has always been done with references to the parts of human body. The author asserts that the phraseological unit with somatism «mouth» is the most widely used one in Solomon’s proverbs.